The nature of psychopathology - Henrik Larsson; Erik Pettersson (Wiley, 2022)
Abstract Readers of JCPP Advances known that the dominant classification system (Diagnostic and Statistical Manual of Mental Disorders) in psychiatry and psychology conceptualizes psychopathology as discrete diagnostic categories. This measurement model builds on a strong assumption of a clear discontinuity between individuals who meet criteria for a diagnosis and those who don't fulfill diagnostic criteria. During the past decades we have seen huge efforts to test this assumption and explore alternative models, such as research from the hierarchical taxonomy of psychopathology consortia. Key findings of these efforts are reviewed and discussed in the December issue of JCPP Advances.